A Fatal Case of Poisoning with Fentanyl Transdermal Patches in Japan. Issue 6 (24th July 2019) - Nara, Akina; Yamada, Chiho; Saka, Kanju; Kodama, Takanori; Yoshida, Masaki; Iwahara, Kaori; Takagi, Tetsuya
Abstract: Fentanyl transdermal patches have been used to treat cancer‐ and noncancer‐related chronic pain. However, its inappropriate or illegal application may cause fatal poisoning. We herein present the case of a Japanese woman in her 40s who was found dead with seven 25‐μg/h fentanyl transdermal patches on her body. We established a detailed toxicological analysis procedure to quantify fentanyl, and its metabolite norfentanyl, and other drugs (acetaminophen, allylisopropylacetylurea, celecoxib, estazolam, promethazine, and sertraline) in human whole blood by ultra‐high‐performance liquid chromatography–tandem mass spectrometry. The measured fentanyl and norfentanyl concentrations in the femoral and cardiac blood were 0.051 and 0.072 μg/mL and 0.033 and 0.076 μg/mL, respectively. The decedent's fentanyl concentrations were consistent with previously reported postmortem blood levels for fatal cases of poisoning by fentanyl transdermal patches. Based on the decedent's case history, autopsy findings, and toxicological analyses, the cause of death was identified as intoxication with transdermal fentanyl.